2001
DOI: 10.3354/dao044133
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Microcotyle sebastis infestation in cultured rockfish Sebastes schlegeli by oral administration of praziquantel in combination with cimetidine

Abstract: The effect of cimetidine on the treatment efficacy of praziquantel against Microcotyle sebastis infestation in cultured rockfish Sebastes schlegeli was investigated. Juvenile rockfish were divided into 7 groups, and orally administered praziquantel alone (50, 100 and 200 mg kg -1 body wt, BW) or in combination with cimetidine at a dose of 200 mg kg -1 BW for each praziquantel dose. The fish in the control group were administered only saline. The results clearly showed that coadministration of cimetidine with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
1
16
1
1
Order By: Relevance
“…The results of the present study agree with a previous report which indicated that coadministration of cimetidine with praziquantel led to a significantly increased treatment efficacy of the latter drug against Microcotyle sebastis infestation in rockfish Sebastes schlegeli (Kim et al 2001a). Moreover, in the present study we first demonstrated in fish that these increased treatment efficacies by cimetidine supplementation were through elevation of praziquantel concentration in the blood of treated fish.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study agree with a previous report which indicated that coadministration of cimetidine with praziquantel led to a significantly increased treatment efficacy of the latter drug against Microcotyle sebastis infestation in rockfish Sebastes schlegeli (Kim et al 2001a). Moreover, in the present study we first demonstrated in fish that these increased treatment efficacies by cimetidine supplementation were through elevation of praziquantel concentration in the blood of treated fish.…”
Section: Discussionsupporting
confidence: 82%
“…Although Kim et al (2001a) have reported that coadministration of cimetidine with praziquantel led to a significantly increased treatment efficacy of the latter drug against Microcotyle sebastis, there are no experimental data on the pharmacokinetic interactions between praziquantel and cimetidine in fish. Therefore, ABSTRACT: The effect of cimetidine on the praziquantel concentration in the blood of the rockfish Sebastes schlegeli and the consequent effect on the treatment efficacy against Microcotyle sebastis were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Praziquantel is a parasiticide that is effective against tapeworms, monogeneans, and trematodes (Buchmann 1987;Mitchell 1995;Kim et al 2001;Sharp et al 2004). It was the first anthelminthic to fulfil the WHO requirements for population-based chemotherapy to treat a broad range of parasitic infections (Wegner 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated its effect on the polyopisthocotyleans Microcotyle sebastis (Kim et al 1998, 2001, Kim & Cho 2000, Kim & Kim 2002, Heterobothrium okamatoi (Hirazawa et al 2000) and Sparicotyle chysophrii (Sitjà-Bobadilla et al 2006), as well as the monopisthocotyleans Gyrodactylus sp. (Tojo & Santamarina 1998) and Neobenedenia girellae (Hirazawa et al 2004).…”
Section: Introductionmentioning
confidence: 99%